Pengaruh Ekstrakurikuler Bahasa Jepang terhadap Hasil Belajar Bahasa Jepang Siswa - Anggun Fadilla Sitompul; Nova Yulia (Universitas Negeri Padang, 2025)
According to the results of the researcher's observations in class XII F.1 and F.2 SMA Negeri 3 Bukittinggi, there are several students who are actively involved in extracurricular activities Nihongo Kurabu. However, this makes a significant difference to student grades in class. Those who participate in Nihongo Kurabu extracurricular activities get higher grades than those who do not participate. The researcher assumes that Nihongo Kurabu extracurricular activities have an influence on student learning outcomes. The research used is quantitative research with correlational research type. The research population was all XII grade students of SMA Negeri 3 Bukittinggi who participated in Nihongo Kurabu extracurricular activities. While the research sample was class XII F.1 and F.2 students who participated in Nihongo Kurabu extracurricular activities as many as 11 students. The design used is the documentation of UAS scores for variable Y (learning outcomes) and questionnaires for variable X (extracurricular activities). The results of the study are as follows: First, students' response to Nihongo Kurabu is in the very strong category, which is 85%. Then student learning outcomes have a good average of 87. From these results it can be concluded that the majority of students' Japanese language learning outcomes are good. Keywords: Influence, Extracurricular Activities, Learning Outcomes.